2012
DOI: 10.5858/arpa.2012-0042-oa
|View full text |Cite
|
Sign up to set email alerts
|

Root Cause Analysis of Problems in the Frozen Section Diagnosis of In Situ, Minimally Invasive, and Invasive Adenocarcinoma of the Lung

Abstract: Context.-Frozen sections can help determine the extent of surgery by distinguishing in situ, minimally invasive, and invasive adenocarcinoma of the lung.Objective.-To evaluate our experience with the frozen section diagnosis of these lesions using root-cause analysis.Design. Results.-There were no false-positive diagnoses of malignancy. Frozen section errors and deferrals were identified in 12.1% (27 of 224) and 6.3% (14 of 224) of the cases, respectively. Significantly more errors occurred in the diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 21 publications
1
59
0
Order By: Relevance
“…With regard to AIS, MIA, and LPA, 79% of the interpretations using frozen sections were accurate for LPA; however, only 41.3% were accurate for MIA, and more than half (52%) of the interpretations were overdiagnoses of invasive adenocarcinoma. Our findings concurred with the recent study by Walts et al . In their study, only 46% of MIAs were accurately recognized in frozen sections, and there were 9% deferrals and 46% frozen section errors in cases of MIA.…”
Section: Discussionsupporting
confidence: 93%
“…With regard to AIS, MIA, and LPA, 79% of the interpretations using frozen sections were accurate for LPA; however, only 41.3% were accurate for MIA, and more than half (52%) of the interpretations were overdiagnoses of invasive adenocarcinoma. Our findings concurred with the recent study by Walts et al . In their study, only 46% of MIAs were accurately recognized in frozen sections, and there were 9% deferrals and 46% frozen section errors in cases of MIA.…”
Section: Discussionsupporting
confidence: 93%
“…Walts and Marchevsky10 reported that section quality and the diagnostic experience of the pathologist were significant factors that affected the accuracy of diagnoses based on frozen sections. For these reasons, some modified procedures were used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Walts and Marchevsky10 found that intraoperative frozen sections had a much lower diagnostic accuracy for AIS and MIA than invasive adenocarcinoma (50.68% vs 96.69%). In a retrospective analysis of pulmonary nodules with a diameter <1.5 cm from 183 patients, Marchevsky et al 11 found that the sensitivity of diagnoses based on intraoperative frozen sections was quite low for tumours with a diameter <1.1 cm.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the strict sense, the definitive delineation of microinvasive foci is not critical from the clinical viewpoint (see below). intraoperative consultation of more than one pathologist necessary; more than one sample of frozen sections needed) as demonstrated by root cause analysis of 224 consecutive cases [34]. In addition, Yeh et al [33 & ] demonstrated that not only invasion per se but also different stromal invasion categories in combination with specific ADC patterns were associated with variations in patient survival.…”
Section: Minimally Invasive Adenocarcinomamentioning
confidence: 99%